Antiphospholipid Antibodies Alter Cell‐Death‐Regulating Lipid Metabolites in First and Third Trimester Human Placentae. (9th April 2015) - Pantham, Priyadarshini; Heazell, Alexander E.P.; Mullard, Graham; Begley, Paul; Chen, Qi; Brown, Maria; Dunn, Warwick B.; Chamley, Lawrence W.
<x xml:space="preserve">Abstract</x> Problem Antiphospholipid antibodies (aPL) are maternal autoantibodies that increase the risk of a woman developing preeclampsia 10‐fold. aPL are internalized into the syncytiotrophoblast and increase extrusion of necrotic trophoblast debris into the maternal blood. This necrotic trophoblast debris may trigger endothelial cell dysfunction contributing to the pathogenesis of preeclampsia. We hypothesize that aPL directly affect placental metabolism, leading to increased syncytiotrophoblast death. Methods of study First and third trimester human placental explants were cultured with aPL, a control antibody, or media only, and placental conditioned culture media was examined by mass spectroscopy. Molecular targets of interest were investigated using qRTPCR and immunohistochemistry. Results The levels of 79 and 132 metabolites, respectively, were altered due to the treatment of first and third trimester placental explants with aPL. These included ceramides and diacylglycerols, which play important roles in cell death regulatory pathways. Antiphospholipid antibodies also decreased the expression of protein kinase C‐epsilon (PRKCE) in placental explants, possibly due to the disrupted balance between ceramides and diacylglycerols caused by aPL. Conclusion One mechanism by which aPL cause aberrant cell death in the syncytiotrophoblast in the first and third trimester is by disruption of placental lipid signaling and decreased expression of PRKCE.